Pelatihan Perpajakan dan Pelaporan Keuangan UMKM Di Kelurahan Mijen Kecamatan Mijen Kota Semarang - Muchayatin Muchayatin; Camelius Isodorus Ikut; Rr. Suprantiningrum; Dian Evianika Rusati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
In the era of globalization and technological advancement, the role of (MSMEs) in the economy is becoming increasingly important. However, the problem of the inability of MSMEs to make financial statements and fulfill their tax obligations results in difficulties accessing capital, where MSMEs cannot meet the requirements in obtaining capital through banks or other financial institutions. This community service aims to provide literacy to individual taxpayers of MSMEs who have not carried out their tax obligations correctly, especially related to changes from PP 23 of 2018 to the Law on Harmonization of Tax Regulations (HPP) of 2020. The methods used are counseling and socialization regarding aspects of taxation and financial reporting to MSMEs. The results obtained in the discussion showed that the limit of non-taxable gross circulation is Rp. 500,000,000 following the Law on Harmonization of Tax Regulations (HPP) of 2020.